Pandangan Fikh Siyasah Terhadap Larangan Rangkap Jabatan Wakil Menteri Dalam Pemerintahan Indonesia - Anggia Putri Syarani; Helena Syifa NST; Risky Azhari Selian; Cindy Aulia Rahma Batu Bara; Adrian Riyoeda Z.DS (Tabayyun : Journal Of Islamic Studies, 2023)
As a country with a majority Muslim population, Indonesia faces unique challenges in harmonizing the principles of Siyasah Fiqh with a secular government system. Efforts to understand and adapt Islamic principles to government policies are an important step in achieving this harmonization. Comparison with practices in other Muslim countries can provide additional insight into the suitability and sustainability of the policy of prohibiting multiple positions in Indonesia. Indonesia's government system, which adheres to a